Acute kidney injury in hospitalized adults with chronic kidney disease: comparing cROCK, KDIGO, and combined criteria - Ling Sun; Rui-Xue Hua; Yu Wu; Lu-Xi Zou (Kidney Research and Clinical Practice, 2023)
Background Acute-on-chronic kidney disease (ACKD) increases the risk of progression of chronic kidney disease (CKD). This study aimed to evaluate the ability of a novel criteria of reference change value of the serum creatinine optimized criteria for acute kidney injury in CKD (cROCK) to detect ACKD patients. Methods This was a retrospective observational study with a 3-year follow-up. All included patients with CKD stage 3 were evaluated using cROCK, Kidney Disease Improving Global Outcomes (KDIGO), and their combined criteria. The renal composite endpoints, major adverse cardiovascular events (MACEs), and all-cause mortality were recorded as clinical outcomes. Results A total of 812 patients was enrolled. The cROCK criteria detected more ACKD events than did the KDIGO (68.0% vs. 59.5%, p < 0.001). Compared to KDIGO (−) & cROCK (−) group, ACKD patients diagnosed by cROCK had significantly higher hazard ratio [HR] for renal composite endpoints (HR, 3.591; p < 0.001), MACEs (HR, 1.748; p < 0.001), and all-cause mortality (HR, 2.985; p < 0.001). The patients in KDIGO (+) & cROCK (+) group had the lowest survival probability when considering renal composite endpoints, MACEs, and all-cause mortality (all p < 0.001). Furthermore, cROCK resulted in the largest area under the receiver operating characteristic curve (AUC) for predicting renal composite endpoints, and the combined criteria led to the largest AUC for predicting MACEs and all-cause mortality. Conclusion Compared to the KDIGO, the cROCK detected more ACKD events. Combining both cROCK and KDIGO criteria might improve the predictive ability for long-term outcomes in ACKD patients.